AGE AND PEDAGOGICAL PSYCHOLOGICAL PROBLEMS OF BEHAVIORAL SELF-AWARENESS IN ADOLESCENTS - Mamanazarov, Uchqun (Educational Research in Universal Sciences, 2024)
This article aims to investigate the relationship between age and pedagogical psychological problems associated with behavioral self-awareness in adolescents. The study examines the challenges that adolescents face in developing and maintaining self-awareness and how these issues impact their educational experiences. Using a mixed-methods approach, including surveys, interviews, and literature review, the research explores the interplay between age-related factors and the development of behavioral self-awareness. The findings provide valuable insights for educators, psychologists, and parents in promoting healthy self-awareness among adolescents and optimizing their educational outcomes.